Desenvolvimento de eletrodo modificado com filme de poli(1-aminoantraceno) para determinação de dopamina em formulação farmacêutica - Troiani, Estela de Pieri (Universidade Federal de São Carlos, 2007)
The aim of this work was to study the electrochemical response of the electrode modified with poly(1-aminoanthracene) (PAA) for dopamine (DA) determination by means of cyclic voltammetry and differential pulse voltammetry measurements. The PAA were electropolymerized on platinum electrodes and conducting glass ITO, by cyclic voltammetry in a solution of 0.01 mol L-1 1- aminoanthracene and 0.1 mol L-1 tetrabutylammonium perchlorate (TBAP) or 0.1 mol L-1 lithium perchlorate (LiClO4) in acetonitrile medium, being that the best results for DA determination was obtained with Pt/PAA electrode prepared with TBAP. The parameters applied in differential pulse voltammetry were a = 0.1 V, Ei = 0.002 V and ν = 0.002 V s-1. The solution used for DA determination was phosphate buffer solution pH 6.0. The method was applied to determine DA. The system showed a good response for DA when a conditional potential of -0.7 V was applying for 3 s before the cyclic voltammetry. With this pre-treatment the PAA electrode presented a permselective response for DA with no interference of ascorbic acid (AA). The system was available for DA determination by means of differential pulse voltammetry and detection and quantification limits of 4.64 μmol L-1 and 15.4 μmol L-1, respectively, were obtained. A recovery of 99.7-104% was found. The precision of the method was checked by performing ten successive measurements of a 5.0x10-4 mol L-1 DA solution and a relative standard deviation (RSD) of 1.2% were achieved. The analysis of the morphology of PAA film by SEM and FEG showed a flat structure indicating a compact and smooth film. By AFM the film morphology presented small spherical structures with maximum height of about 18 nm indicating that the film is nanostructured. The electrode stored dry presented biggest life-time and better analytical response. In the present study, the PAA electrode showed as a very interesting system for DA determination in pharmaceutical formulation with no interference of AA.
Keywords: Métodos eletroanalíticos; Dopamina; Polímeros condutores; Poli(1-aminoantraceno); CIENCIAS EXATAS E DA TERRA::QUIMICA